Isotretinoin does not contribute to increased neuropsychiatric risk in the overall acne population, but risk management during treatment remains essential. (21st April 2022) - Ravencroft, Jane; Eichenfield, Lawrence
Abstract : Linked Article: Paljarvi et al. Br J Dermatol 2022; 187:64–72 .